Internalisasi Nilai-Nilai Akhlaqul Karimah dalam Pendidikan Dasar di SD IT Al Falaah Sambi Boyolali (Studi Analisis Aksiologi Filsafat Islam) - Hidayatul Chasanah; Mujiburrohman Mujiburrohman (TSAQOFAH, 2026)
Although the internalization of ethical values and character has received attention in various studies, research that specifically discusses the internalization of akhlaqul karimah values in elementary school teaching and learning activities through the axiological perspective of Islamic philosophy remains limited. This study aims to examine the process of internalizing akhlaqul karimah values in teaching and learning activities at SD IT Al Falaah Sambi Boyolali using the axiological perspective of Islamic philosophy. This study employed a descriptive qualitative approach with a case study method. This approach was chosen to explore in depth the process of internalizing akhlaqul karimah values in the basic education environment. Data were collected through interviews, observation, and documentation, and were then analyzed using an interactive qualitative approach. The findings show that the internalization of akhlaqul karimah values at SD IT Al Falaah Sambi Boyolali takes place through various school activities, such as the tahfidz program, the qiroa’ati program, and learning activities. These findings affirm that akhlaqul karimah values can be systematically internalized through the integration of religious activities and the learning process. The conclusion of this study indicates the importance of internalizing akhlaqul karimah values for shaping the character of elementary school students. The implications of this study provide a theoretical contribution to the development of literature on the internalization of akhlaqul karimah values in basic education, as well as a practical reference for educational institutions and teachers in developing Islamic value-based learning. This study also opens opportunities for further research on the axiological analysis of Islamic philosophy in other educational aspects.